2018
DOI: 10.1007/s12028-017-0488-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Admission Hypertension on Rates of Acute Kidney Injury in Intracerebral Hemorrhage Treated with Intensive Blood Pressure Control

Abstract: Our study observed higher rates of AKI in patients presenting with severe hypertension. Further research is needed to determine the most appropriate strategies for managing blood pressure in ICH patients presenting with higher SBP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…Organ function decreases with age, and is accompanied by the onset of arteriosclerosis, diabetes and hypertension, which may increase susceptibility to AKI. We revealed that hypertension was one of the independent risk factors for AKI in RM patients; likewise, a previous study reported that diagnosed hypertension was an independent risk factor for AKI in patients with chronic kidney disease or intracerebral hemorrhage [19,20]. In addition, a retrospective study of 43,611 patients demonstrated that the occurrence of AKI in hospitalized, previously normotensive adults was independently associated with increased blood pressure during the first 2 years after discharge [21].…”
Section: Discussionsupporting
confidence: 67%
“…Organ function decreases with age, and is accompanied by the onset of arteriosclerosis, diabetes and hypertension, which may increase susceptibility to AKI. We revealed that hypertension was one of the independent risk factors for AKI in RM patients; likewise, a previous study reported that diagnosed hypertension was an independent risk factor for AKI in patients with chronic kidney disease or intracerebral hemorrhage [19,20]. In addition, a retrospective study of 43,611 patients demonstrated that the occurrence of AKI in hospitalized, previously normotensive adults was independently associated with increased blood pressure during the first 2 years after discharge [21].…”
Section: Discussionsupporting
confidence: 67%
“…However, we derived this definition from other studies in those with severe neurologic injuries that have recently been published in the literature. [32][33][34] Our results should not be generalized to patients with CKD or those who present with an AKI. We are also unable to report data related to overall fluid status due to limitations in abstracting this retrospectively from the electronic medication record.…”
Section: Discussionmentioning
confidence: 88%
“…This could explain the higher incidence of renal adverse events found in the study . Subsequent trials shed further light on the safety of acute BP lowering in patients with ICH . One retrospective analysis showed that an SBP reduction of more than 90 mm Hg increases the risk of acute kidney injury (AKI) irrespective of previous kidney function .…”
Section: Blood Pressure Control In Neurologic Emergenciesmentioning
confidence: 84%
“…One retrospective analysis showed that an SBP reduction of more than 90 mm Hg increases the risk of acute kidney injury (AKI) irrespective of previous kidney function . Another analysis evaluated the impact of the degree of admission hypertension on renal outcomes in this patient population . Patients with severe hypertension (SBP of 220 mm Hg or higher) were found to have higher rates of AKI compared with patients with mild or moderate admission hypertension.…”
Section: Blood Pressure Control In Neurologic Emergenciesmentioning
confidence: 99%
See 1 more Smart Citation